DETERMINATION OF CYTOTOXIC EFFECTS OF PROCHLORAZ AND TRALKOXYDIM IN BARLEY (HORDEUM VULGARE L.) ROOTS - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2018)
The effects of prochloraz (fungicide) and tralkoxydim (herbicide) on the root morphology, root growth, mitotic index and chromosomal behaviour were analysed in a non-target plant, barley (Hordeum vulgare L.). The commercial and higher doses of prochloraz (40, 80 and 120 mu M) and tralkoxydim (50, 100 and 150 mu M) were applied to barley roots up to 60-h. Some morphological defects such as grey regions and tumours occurred on the root tips of barley treated with the prochloraz and tralkoxydim, respectively. Besides the root elongation and mitotic indices were inhibited by the treatment with the two pesticides time and dose dependently. Various types of mitotic aberrations such as chromosome bridges, stickiness, laggards, mono polarity, c-mitosis, abnormal metaphase and anaphase were observed in prochloraz and tralkoxydim treated barley root tips. Based on our results, tralkoxydim is more toxic to barley roots in comparison to prochloraz. In conclusion, the two pesticides, prochloraz and tralkoxydim may be harmful to non target organisms even their commercial and higher concentrations.
Keywords: Chromosomal abnormalities; Fungicide; Herbicide; Mitotic index; Root growth; PESTICIDES; STRESS